Comparing tactical behaviour of soccer players in 3 vs. 3 and 6 vs. 6 small-sided games - Silva, B.; Garganta, J.; Santos, R.; Teoldo, I. (Journal of Human Kinetics, 2014)
The present study aimed to compare players' tactical behaviour in 3 vs. 3 and 6 vs. 6 soccer small-sided games (SSGs). The sample comprised 3,482 tactical actions performed by 18 U-11 youth soccer players from a Portuguese club, in 3 vs. 3 and 6 vs. 6 SSGs. All participants played eight minutes in both situations and field size was adapted according to the number of players involved (30 m x 19.5 m for 3 vs. 3 and 60 m x 39 m for 6 vs. 6). The System of Tactical Assessment in Soccer (FUT-SAT) was used for data collection and analyses. Descriptive analysis was conducted to verify frequencies and percentages of the variables assessed. The chi-squared (ƒÔ2) test was performed to compare the frequencies of the variables between 3 vs. 3 and 6 vs. 6 SSGs and Standardized Residuals (e) were used to examine the influence of the frequency of one or more variables within 3 vs. 3 and 6 vs. 6 SSGs. Data treatment was performed through SPSS for WindowsR, version 18.0. Results indicated that players displayed safer behaviours in 6 vs. 6 SSG and more aggressive behaviours in 3 vs. 3 SSG. Findings can aid coaches and teachers to develop different players' tactical skills according to the chosen SSG (3 vs. 3 or 6 vs. 6) form.